Cardiovascular-Renal Changes After Kidney Donation. Issue 4 (April 2015) - Yilmaz, Banu Avcioglu; Caliskan, Yasar; Yilmaz, Akar; Ozkok, Abdullah; Bilge, Ahmet Kaya; Deniz, Gunnur; Sariyar, Muzaffer; Yildiz, Alaattin
<x xml:space="preserve">Abstract</x> Background Long-term consequences of kidney donation are not well known. Most of the studies published were focused on renal risk. In this prospective study, we investigated the changes in cardiovascular function after kidney donation. Methods Thirty-eight living kidney donors were included. In addition to 24-hr ambulatory blood pressure monitoring, serum interleukin-6, vascular cell adhesion molecule (VCAM), and asymmetric dimethylarginine levels were measured. Endothelial function was examined by measuring ischemia-induced flow-mediated dilation (FMD) of the brachial artery. All studies were repeated at 3 months and 12 months after kidney donation. Results The mean serum interleukin-6 levels, both at 3 months and 12 months, were significantly increased as compared to the baseline (P = 0.007 and P < 0.001, respectively). The mean serum asymmetric dimethyl-arginine (P < 0.001) and VCAM levels (P < 0.001) at 12 months were significantly increased as compared to baseline. FMD values at 1 year (9.3% ± 7.1%) were significantly decreased as compared to 3 months (13.0% ± 6.0%, P = 0.001) and baseline (13.9% ± 6.3%, P = 0.002). In multivariate analysis, serum uric acid (P = 0.001), estimated glomerular filtration rate (P = 0.027), and VCAM (P = 0.014) levels were the independent predictors of FMD 12 months after kidney donation. Conclusion Our findings suggest that kidney donation might increase the cardiovascular risk in kidney donors.